TINJAUAN YURIDIS MENGENAI WANPRESTASI PERJANJIAN PENGANGKUTAN (STUDI KASUS ANTARA PT. GREATWALL DRILLING ASIA PASIFIK DAN PT PRIMA SAMUDERA ZONA TRANS) - Hanny, Faisal (Fakultas Hukum Universitas Trisakti, 2023)
An agreement is an act in which one or more people bind themselves to one or more people, agreements are regulated in Book III of the Civil Code where Chapters 1-4 regulate agreements in general and Chapters 5-18 regulate agreements specifically, while Article 1338 of the Civil Code states that all agreements made legally apply as law for the parties who make them. The conditions for the validity of an agreement are regulated in article 1320 of the Civil Code, which includes fulfilling the elements of agreement, skill, a certain thing and lawful causes. The validity of a land transportation agreement is based on the above statutory regulations and as the lex specialist is Law Number 22 of 2009 concerning Road Traffic and Transportation where the limit of compensation for transportation organizers is regulated in Chapter X Article 188, while the research method used used by the author is descriptive normative legal research taken from secondary and primary data. From the basis of the writing above, the author sees that there is a discrepancy between the facts that occurred in the transportation agreement between PT Greatwall Drilling Asia Pacific and PT Prima Samudera Zona Trans, which apart from being subject to the Civil Code because it relates to transportation, must be subject to Law Number 22 of 2009 concerning Road Traffic and Transportation in force in the Republic of Indonesia.